2017
DOI: 10.3892/ol.2017.7454
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diet‑induced adipokine and cytokine alterations promote the progression of prostate cancer in�vivo and in�vitro

Abstract: High-fat diet (HFD) -induced obesity is associated with more aggressive and lethal prostate cancer (PCa) in males, although the exact underlying mechanisms remain unclear. In the present study, transgenic adenocarcinoma of mouse prostate (TRAMP) models fed on an HFD (40% fat) or a control diet (CD; 16% fat) were generated, and cancer differentiation, local invasion and metastasis were compared at 20, 24 and 28 weeks. Mouse sera from each group were collected, and adipokines and cytokines were measured using mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…Alternatively, pro-tumourigenic factors could be altered by FA levels and saturation. It has been shown that fatty acids induce the expression and secretion of inflammatory cytokines such as IL-6, IL-8 and IL-1β via activation of NF-κB pathway in normal and cancer cells 45 47 . Indeed, our data revealed that C75 treatment suppressed the activation of NF-κB in post-slippage cells which supports the notion that increased FASN promotes the induction of post-slippage secretory factors.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, pro-tumourigenic factors could be altered by FA levels and saturation. It has been shown that fatty acids induce the expression and secretion of inflammatory cytokines such as IL-6, IL-8 and IL-1β via activation of NF-κB pathway in normal and cancer cells 45 47 . Indeed, our data revealed that C75 treatment suppressed the activation of NF-κB in post-slippage cells which supports the notion that increased FASN promotes the induction of post-slippage secretory factors.…”
Section: Discussionmentioning
confidence: 99%
“…Sectioning, deparaffinization and rehydration of tumor tissue samples was performed as previously described (32). Tumor tissue samples were stained for histological changes using haemotoxylin and eosin (H&E) staining.…”
Section: Haematoxylin and Eosin Stained Tumor Tissuementioning
confidence: 99%
“…Heterozygous TRAMP female mice (purchased from Jackson Laboratory, Bar Harbor, ME) were bred to non‐transgenic C57BL/6 male mice (Jackson Laboratory). The second‐generation TRAMP female mice and non‐transgenic male mice were selected by genotyping as previously reported . After weaning (postnatal day 21, P21), TRAMP female mice were randomly categorized into two groups and fed either control diet (16% of calories from fat, SLAC Inc., http://www.slaccas.com; Shanghai, China) or HFD (40% of calories from fat, SLAC Inc.,) before mating, during pregnancy, and into lactation (Table ).…”
Section: Methodsmentioning
confidence: 99%